Pengaruh Manajemen Strategi dan Perilaku Kerja Inovatif Terhadap Kinerja Kontekstual Pegawai Di Perguruan Tinggi Swasta Kota Medan - Supriadi, Supriadi (Manajemen dan Bisnis, 2025)
This research aims to determine and analyze the influence of strategic management and innovative work behavior on employee contextual performance at Medan City Private Universities. With well developed strategic management and supported by innovative work behavior from employees, it will have an impact on improving contextual performance. The research method in this research is a quantitative method by distributing questionnaires. Data analysis techniques use descriptive analysis and part analysis. The research results show that strategic management and innovative work behavior have a significant effect on performance. Recommendations in this research are that it is hoped that Medan City Private Universities will have good strategic management in carrying out the Tri Dharma Perguruan Tinggi, and that employees as individuals who provide services to students and lecturers will have innovative work behavior. For further research, it would be possible to add other variables if you want to measure employee contextual performance at private universities, such as promotions and accreditation ratings